TI_GERICHTE 12.2012.164 vom 29. Oktober 2013 , Riconoscimento di debito - disconoscimento di debito - legittimazione delle parti - TI Tribunale d'appello (2013)
Riconoscimento di debito - disconoscimento di debito - legittimazione delle parti